1984
DOI: 10.1021/bi00316a004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of template conversion from the B to the Z conformation on RNA polymerase activity

Abstract: Transition from the right-handed B to the left-handed Z conformation of DNA was studied by circular dichroism in parallel with the ability of the DNA to support RNA synthesis with Escherichia coli RNA polymerase. Since the B to Z transition is generally induced by a chemical agent, a definitive demonstration that a change in activity is due to the conformational change, and not to the agent itself or to other factors, requires the clear-cut correlation of template activity and conformation under a variety of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
3
17
1
Order By: Relevance
“…The reported ratio is 3.2 for Z-form and 8.5 for B-form poly(dG-dC) (1). It had been previously shown that under the experimental conditions employed here there is little if any aggregation of Z-poly(dG-dC) (15). Indeed the ultraviolet absorbance and circular dichroism spectra were those expected for the Z-form of poly(dG-dC) with no absorbance at wavelengths greater than 300 nm nor evidence of scattered uv light due to aggregation (16).…”
Section: Methodssupporting
confidence: 50%
“…The reported ratio is 3.2 for Z-form and 8.5 for B-form poly(dG-dC) (1). It had been previously shown that under the experimental conditions employed here there is little if any aggregation of Z-poly(dG-dC) (15). Indeed the ultraviolet absorbance and circular dichroism spectra were those expected for the Z-form of poly(dG-dC) with no absorbance at wavelengths greater than 300 nm nor evidence of scattered uv light due to aggregation (16).…”
Section: Methodssupporting
confidence: 50%
“…Consistent with this idea, the Z-conformation has been shown to provide a poor template for transcriptional activity with Escherichia coli RNA polymerase (27), and further, the d(C-G)16 sequence in supercoiled plasmids causes a severe block to transcription in vitro (28). This notion is consistent also with the location of alternating purine-pyrimidine tracts in simian virus 40 DNA regulatory sequences that bind anti-Z-DNA antibodies (29), of the d(G-T), tracts at the ends of yeast chromosomes (30) and of the alternating purine-pyrimidine long terminal repeats in mouse mammary tumor virus (31).…”
Section: -64 T-c-c-g-c-g-c-a-c-a-tmentioning
confidence: 82%
“…Previous studies from this and other laboratories have shown that synthetic Z DNA helices are relatively poor substrates for Escherichia coli RNA polymerase (van de Sande and Jovin, 1982;Butzow et al, 1984). Furthermore, in experiments cited in Rich et al (1984), d(G-C)n tracts within a transcribed gene (in negatively supercoiled plasmid molecules) lead to termination of transcription.…”
Section: Advantages Of High Resolution Darkfield Em Of Native Dna-iggmentioning
confidence: 90%